2006
DOI: 10.1346/ccmn.2006.0540111
|View full text |Cite
|
Sign up to set email alerts
|

Weathering sequences of rock-forming minerals in a serpentinite: Influence of microsystems on clay mineralogy

Abstract: Under closed geochemical conditions, the weathering of a serpentinite rock composed of serpentine (70–85%) and magnesian chlorite (10–15%) associated with magnetite and chromite leads to the complete replacement of serpentine and chlorite by 2:1 layer silicates and produces new Fe oxides. The serpentine minerals crystallize under different habits issued from the serpentinization processes: mesh and hourglass pseudomorphic textures were formed from olivine, and thin-bladed pseudomorphic textures from pyroxene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…No correlation was in fact found between Ni E or Ni ex and the total Fe oxides that are mostly of lithogenic origin as indicated by the low variability among soil horizons and should therefore have a low specific surface area (Schwertmann and Taylor 1989). Smectites contribute to Ni sorption and form during the very first steps of serpentine weathering (Caillaud et al 2006), but only seldom did we find swelling minerals in these Entisols and Inceptisols. The presence of swelling minerals, with high cation exchange capacity, apparently did not induce any difference in the Ni E and Ni ex concentrations (p=0.538 and 0.873, respectively, n=8, oneway Anova), thus indicating that also the extractable forms are linked to the composition of the parent material in these poorly developed soils.…”
Section: Discussionmentioning
confidence: 87%
“…No correlation was in fact found between Ni E or Ni ex and the total Fe oxides that are mostly of lithogenic origin as indicated by the low variability among soil horizons and should therefore have a low specific surface area (Schwertmann and Taylor 1989). Smectites contribute to Ni sorption and form during the very first steps of serpentine weathering (Caillaud et al 2006), but only seldom did we find swelling minerals in these Entisols and Inceptisols. The presence of swelling minerals, with high cation exchange capacity, apparently did not induce any difference in the Ni E and Ni ex concentrations (p=0.538 and 0.873, respectively, n=8, oneway Anova), thus indicating that also the extractable forms are linked to the composition of the parent material in these poorly developed soils.…”
Section: Discussionmentioning
confidence: 87%
“…Spheroidal weathering is quite a common result of chemical weathering; it involves corestones (i.e., spheroids of relict bedrock) of various compositions and sizes, which are surrounded by concentric shells, i.e., rindlets, arranged in zones. Though mechanisms and agents of chemical and spheroidal weathering are still discussed, these processes are fairly well characterized from various geological settings (e.g., Claridge & Campbell, 1984;Pokrovsky et al, 2005;SoubrandColin et al, 2005;Caillaud et al, 2006;Velbel, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Additional results (Caillaud et al, 2006) showed that such mineralogical complexity arises from the heterogeneity of the serpentine textures in the rock, the occurrence of additional rockforming minerals (chlorite and oxides) and the diversity of their corresponding weathering microsites (with specific morphological, mineralogical and chemical characteristics) in the profile.…”
Section: Introductionmentioning
confidence: 99%